Novel tetrahydronaphthalen-1-yl-phenethyl ureas: synthesis and dual antibacterial-anticancer activities - Yusuf Akbaba; Fatma Necmiye Kacı; Mehmet Enes Arslan; Süleyman Göksü; Adil Mardinoğlu; Hasan Türkez (Journal of Enzyme Inhibition and Medicinal Chemistry)
Cancer and antibiotic-resistant bacterial infections are significant global health challenges. The resistance developed in cancer treatments intensifies therapeutic difficulties. In addressing these challenges, this study synthesised a series of N,N′-dialkyl urea derivatives containing methoxy substituents on phenethylamines. Using isocyanate for the efficient synthesis yielded target products 14–18 in 73–76% returns. Subsequently, their antibacterial and anticancer potentials were assessed. Cytotoxicity tests on cancer cell lines, bacterial strains, and a healthy fibroblast line revealed promising outcomes. All derivatives demonstrated robust antibacterial activity, with MIC values ranging from 0.97 to 15.82 µM. Notably, compounds 14 and 16 were particularly effective against the HeLa cell line, while compounds 14, 15, and 17 showed significant activity against the SH-SY5Y cell line. Importantly, these compounds had reduced toxicity to healthy fibroblast cells than to cancer cells, suggesting their potential as dual-functioning agents targeting both cancer and bacterial infections.